1998
DOI: 10.1093/tropej/44.6.320
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels in children with neurological disorders

Abstract: Blood lead levels were measured by atomic absorption spectrometry in 82 children suffering from various neurological disorders (cerebral palsy 42, seizure disorders 35, acute encephalopathy of unknown origin 5) and in 28 healthy children, aged 1 to 12 years. Mean blood lead levels were 11.96 +/- 10.97 micrograms/dl in control children and 19.30 +/- 17.65 micrograms/dl in children with neurological disorders. A significant number of control children as well as those who had neurological disorders were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
3
10
1
Order By: Relevance
“…Recent findings indicate that, in infants and children, encephalopathy may occur at lower blood lead levels than previously reported. 5,6 In the present study, blood lead levels of children with neurological disorders was 18.6 µg/dl. Results of the present study are comparable to data of Kumar et al, 5 where mean blood lead level of children with neurological disorders (cerebral palsy, seizures, and encephalopathy) was 19 µg/dl.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Recent findings indicate that, in infants and children, encephalopathy may occur at lower blood lead levels than previously reported. 5,6 In the present study, blood lead levels of children with neurological disorders was 18.6 µg/dl. Results of the present study are comparable to data of Kumar et al, 5 where mean blood lead level of children with neurological disorders (cerebral palsy, seizures, and encephalopathy) was 19 µg/dl.…”
Section: Discussionsupporting
confidence: 43%
“…5,6 In the present study, blood lead levels of children with neurological disorders was 18.6 µg/dl. Results of the present study are comparable to data of Kumar et al, 5 where mean blood lead level of children with neurological disorders (cerebral palsy, seizures, and encephalopathy) was 19 µg/dl. Rojas et al 6 found blood lead levels of ≥ 18 µg/dl were associated with low muscular strength, decreased osteotendinose reflexes, fine and gross motricity, and hypotonic-muscular tone.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…It was suspected over many years that lead (Pb) poisoning might be associated with ASD [174][175][176][177][178][179][180][181] ; this has been confirmed in some specific cases [182] . Attention has moved to organomercurials (notably methylmercury) found in some immunological reagents, because methylmercury (like TMT) can cause limbic damage in susceptible animal models [183] .…”
Section: Identity Of the Environmental Agent(s)mentioning
confidence: 99%
“…As lots of agricultural lands are subjected to anthropogenic influence foodstuff often contains a maximum permissible dose of heavy metals. In its turn heavy metals which enter an organism with food are especially dangerous because they are in conjunction with biologically-active substances and rather easily penetrate through natural barriers thus violating normal organism functioning [2][3][4]. A characteristic feature of all heavy metals that increases danger is their cumulation and very slow excretion.…”
Section: Introductionmentioning
confidence: 99%